SECOND LANGUAGE PRONUNCIATION INSTRUCTION (Journal of Contemporary Philology, 2019)
The aim of this study is to evaluate the results of the laboratory and classroom-based research studies that investigate the effect of pronunciation instruction. The analysis shows   that   pronunciation   instruction facilitates  modification  of  learners’  L2 pronunciation.    Different    types    of    instruction    develop    different    aspects    of pronunciation   as   a   language   skill;   in   particular,   prosody-focused   instruction considerably  improves  learners’  communicative  performance.   Inaddition,  the corrective  feedback  given  by  the  teacher  is  of  great  significance  for  enhancing learners’ noticing skills and raising their phonological awareness and critical attitude towards their own pronunciation. The  effectiveness of phonetic  instruction suggests that  there  are  long-term  benefits  of  pronunciation  training  if  it  is  systematically incorporated into the teaching practice.
Keywords: speech perception; pronunciation instruction; L2 pronunciation; corrective feedback; phonological awareness